2015
DOI: 10.1515/hukin-2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

The Intricacies of Children’s Physical Activity

Abstract: Understanding the physical activity patterns of youth is an essential step in preparing programming and interventions needed to change behavior. To date, little is known about the intricacies of youth physical activity across various physical activity segments (i.e. in school, out of school, recess, classroom physical activity, physical education, weekends, etc.). Therefore, the purpose of the study was to examine the physical activity patterns of elementary school children across various segments and during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
(51 reference statements)
1
10
0
Order By: Relevance
“…A wide range of instruments were used to determine PAP including accelerometers [ 8 , 9 , 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], pedometers [ 22 , 57 , 58 , 59 , 60 , 61 , 62 ], heart rate monitors [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], questionnaires/diaries [ 10 , 11 , 27 , 72 , 73 , 74 , 75 ...…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of instruments were used to determine PAP including accelerometers [ 8 , 9 , 12 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], pedometers [ 22 , 57 , 58 , 59 , 60 , 61 , 62 ], heart rate monitors [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], questionnaires/diaries [ 10 , 11 , 27 , 72 , 73 , 74 , 75 ...…”
Section: Resultsmentioning
confidence: 99%
“…23,24 In addition, studies have shown the significant decreases in daily physical activity on nonschool days (e.g., weekends), which highlight the importance of the school structure. 25 Alexander and Lyons 26 reported that children in year-round schooling showed significant accelerated gains in BMI during winter compared with previous summers. This study showed mitigated increases in BMI z-scores during summer, but it is unknown how BMI would fluctuate across the winter months.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, students at follow up accumulated more than half of their daily recommendations. Previous studies have suggested that a majority of youth physical activity is accumulated outside of school [32] suggesting that these participants will also be set up to meet daily habitual recommendations.…”
Section: Discussionmentioning
confidence: 99%